Productivity and quality improvement in manufacturing organizations by using industrial engineering techniques - 443737 Chong, Yee Khoon (Sekudai : UTM, 1998)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1998